Professional competencies in the training of higher university aeronautical technicians in Bolivia - Mamani, Oscar Mamani (2024)
Competency-based education in higher education, especially in the field of aeronautics, has become crucial for preparing students for a rapidly changing labor market. This approach aims to develop practical skills and applied knowledge essential for addressing sector challenges. The ICAO’s Tranair Plus (TPP) program standardizes this training in civil aviation, ensuring quality education. This study employs a qualitative approach through a bibliographic review, analyzing academic sources on key competencies such as technical skills, leadership, teamwork, and effective communication. Teaching methodologies such as problem-based learning and project-based learning, which are effective in developing these competencies, are examined, along with evaluation methods like self-assessment and peer assessment. Preliminary results indicate that this model improves the employability of graduates, who acquire skills highly valued in the aeronautical sector, although it faces challenges such as the constant need for updating competencies and a lack of resources. Despite these obstacles, the competency-based approach has shown improvements in professional performance and student motivation. Full implementation of this approach is expected by the end of 2025, and further research is recommended to ensure its long-term effectiveness, strengthening the integration of theoretical knowledge and practical skills in aeronautical education.